Comparison of Oxytocin Massage And Warm Compress Herbal Results In Reducing Uterine Fundus Heightfor Post-Partum Mothers At Tpmb Midwife Rosida Purwakarta Plered 2025 - Dewi Sulastri Sutran; Teti Yuli Handayani; Nurhayati (CV. Inara, 2026)
Postpartum hemorrhage is one of the main causes of high maternal mortality rates and is often associated with slow uterine involution. Various non-pharmacological interventions, such as oxytocin massage and warm herbal compresses, have been developed to stimulate uterine contractions and accelerate the reduction of uterine fundal height (FHH). Objective: This study aims to compare the effectiveness of oxytocin massage and warm herbal compresses on reducing uterine fundal height in postpartum mothers at TPMB Bidan Rosida Plered, Purwakarta Regency. Methods: The study used a quasi-experimental design with a two- group pretest–posttest design. A total of 62 postpartum mothers were selected using accidental sampling technique and divided into two intervention groups, namely oxytocin massage and warm herbal compresses.TFU measurements were performed before and after the intervention. Data were analyzed univariately and bivariately using the Wilcoxon and Mann–Whitney tests with a significance level of p<0.05. Results: Oxytocin massage showed a significant effect on reducing uterine fundal height (p=0.018), while warm herbal compresses did not show a statistically significant effect (p=0.637). However, the Mann–Whitney test results showed no significant difference in effectiveness between the two groups after the intervention (p=0.148). Conclusion: Oxytocin massage was more effective than warm herbal compresses in accelerating the reduction of uterine fundal height in postpartum mothers. Although oxytocin massage provided greater changes in its group, the effectiveness of both interventions was not statistically different directly, so both interventions can be considered as alternative non-pharmacological therapies in postpartum care to support uterine involution and help prevent uterine subinvolution.